2018
DOI: 10.24099/vet.arhiv.160924
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of extensively drug resistant (XDR), extended spectrum beta-lactamases (ESBL) and New Delhi Metallo beta-lactamase-1 (blaNDM1) producing Escherichia coli isolated from a male dog - a case report

Abstract: Molecular characterization of extensively drug resistant (XDR), extended spectrum beta-lactamases (ESBL)and New Delhi Metallo beta-lactamase-1 (blaNDM1) producing Escherichia coli isolated from a male dog -a case report. Vet. arhiv 88, 139-148, 2018.aBSTRaCT In this article, we report the molecular characterization of extensively drug resistant (XDr), extended spectrum, class C beta-lactamases and NDM-1 carbapenemase producing E. coli, isolated from the scrotal fluid of a 3-year-old male dog. In an antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In this study, the ESBL-producing E. coli showed resistance to clinically important antibiotics such as cephalosporins, fluoroquinolones, and aminoglycosides and jeopardize the effective prevention and treatment of various bacterial infections [21]. The present study revealed that all the ESBL-producing E. coli were 100% resistant to cefotaxime and ceftazidime and were concordance with others [11][12][13]. This study reported that the entire ESBL-positive E. coli from piglets as MDR, similarly, in a study from China reported MDR phenotype in total ESBL-producing E. coli isolated from pigs [22].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, the ESBL-producing E. coli showed resistance to clinically important antibiotics such as cephalosporins, fluoroquinolones, and aminoglycosides and jeopardize the effective prevention and treatment of various bacterial infections [21]. The present study revealed that all the ESBL-producing E. coli were 100% resistant to cefotaxime and ceftazidime and were concordance with others [11][12][13]. This study reported that the entire ESBL-positive E. coli from piglets as MDR, similarly, in a study from China reported MDR phenotype in total ESBL-producing E. coli isolated from pigs [22].…”
Section: Discussionsupporting
confidence: 81%
“…The emergence and spread of ESBLs producing E. coli in food-producing animals is a major public health issue worldwide [11][12][13][14][15]. Piglets and farm workers harbored ESBL E. coli, the percentage of cefotaxime and ceftazidime resistance is higher among isolates as compared to ciprofloxacin and chloramphenicol indicates the abundant use of beta-lactam and cephalosporin antimicrobials in piglets and human [5,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several chromosomal and plasmid encoded carbapenemases such as KPC, MBL, Verona integron-encoded MBL (VIM), Imipenem-resistant Pseudomonas (IMP), New Delhi MBL (NDM) and Oxacillinase (OXA) -48, have been documented throughout the world, that could easily be transferred between different enterobacterial species (Stolle et al, 2013;Abraham et al, 2014;Netikul and Kiratisin, 2015). Today, the population of companion animals such as dog and cat is substantially increasing in modern society and the major mechanism of antibiotic resistance among bacterial agents from pets and humans is the exchange of resistance genes (Pruthvishree et al, 2018). Therefore, firm control on infection and surveillance measures combined with prudent use of antibiotics in both human and veterinary practice is essential to reduce the spread of resistance against carbapenems.…”
Section: Introductionmentioning
confidence: 99%
“…). Reports were available in India on ESBL producing and carbapenem resistant E. coli harboring virulence genes in animals(Pruthvishree et al 2017;Nirupama et al 2018;Pruthvishree et al 2018). Plasmid replicon typing of the three blaNDM-5gene-positive E. coli revealed that the NDM gene was on Incl1 plasmid in two isolates (SB27/ 17-CRE, SB28/ 12-CRE) and IncF plasmid was on one isolate (SB28/ 16-CRE).…”
mentioning
confidence: 99%